PENGARUH SISTEM INFORMASI, DATA WAREHOUSE DAN BUSINESS INTELLIGENCE TERHADAP PENGAMBILAN KEPUTUSAN DAN DAMPAKNYA PADA KINERJA ORGANISASI (Studi Kasus Pada BAPPEDA Pemprov DKI Jakarta) - Suharmanto, Suharmanto (POLITEKNIK LP3I JAKARTA, 2019)
Business competition tightened too late to make the company improve itself shifted its competitors. Instead the company that can deliver products and services in accordance with the ever changing customer wishes, he will dominate the competition. The success of a company in the business did not win the competition regardless of the accuracy of the strategy developed by the company. However, in practice, making a decision is not as easy as turning the palm of the hand, when the decision was made incorrectly, it can have a major impact on a company's failure in running the business. The Company specifically BAPPEDA Jakarta government requires a tool capable to understand what the customer really wants, products, and markets. With the construction and development of information systems, data warehouse and business intelligence is the key to Boost profits, minimize costs, better service, and more informed decision-making and ultimately simultaneously an increase in the performance of an effective and efficient organization. In Jakarta Provincial RPJMD Year 2013-2017 conducted by Jakarta Provincial BAPPEDA with indicators that will achieve the availability of baseline data for the planning of economic development, social welfare, urban infrastructure facilities, environmental, civil procedure and sophisticated apparatus. Performance indicators of system development activities supporting the development planning analysis carried out by the UPT center development planning information BAPPEDA Jakarta administration is well-organized data / information development planning is becoming more transparent, integrated easily accessible via the Internet, the availability of development planning information dashboards, reports and interfaces available analysis of data / information that is easy to make a web-based (user friendly). Research shows that all variables have had a significant influence on decision-making and its impact on organizational performance. With path analysis models formed is Y = 0.335 + 0.350 X1 X2 X3 + 0.341 + 0.207 = 0.957 ε1 where R²Yx1x2x3 and Z = 0.244 0.381 X1 + X2 + X3 + 0.591 898 Y + 0,327ε2 where R2 = 0.893 results of this study found that variable Information Systems, Data Warehouse and Business Intelligence provides significant influence on decision-making and simultaneously affect the performance of the organization. Keywords: Information Systems, Data Warehouse, Business Intelligence, Decision Making, Organizational Performance, Information Dashboard, and Path Analysis Interface Report